Open farmland is a hotspot of soil fauna community around facility farmland during a cold wave event - Gao, Meixiang; Jiang, Yige; Sun, Jiahuan; Lu, Tingyu; Zheng, Ye; Lai, Jiangshan; Liu, Jinwen (Frontiers in Sustainable Food Systems, 2023)
In the future, the frequency, duration, and intensity of extreme weather may increase, thus posing a threat to soil biodiversity in farmlands, particularly in agricultural production bases. However, little is known about the effect of cold wave events on the soil fauna community compared with other extreme weathers. Laboratory experiments fail to capture the complicated field environment of cold wave events. We investigated soil fauna communities in facility farmland (strawberry) and open farmland (green cabbage) during a cold wave event in Ningbo City, southeastern China. The results showed that the taxonomic richness of the total soil fauna community in facility farmland was significantly lower than that in open farmland, but the difference in abundance was not significant. The taxonomic richness and body size of soil mites and collembolan communities in facility farmland were significantly lower than those in the open farmland. Obvious differences in abundance, mean body length, mean body width, and ratio of body width to body length of Scheloribatidae, Galumnidae, Onychiuridae, Entomobryidae, and Enchytraeidae were detected between facility farmland and open farmland. The results of this study showed that the taxonomic richness, abundance, and body size of the soil fauna community in open farmland were significantly higher than those in facility farmland during a cold wave event. We suggested that the open farmland could be a “refuge” and “hot spot” of soil fauna community during the cold wave events.